Etiologies of Hospitalized Acute Bronchiolitis in Children 2 Years of Age and Younger: A 3 Years' Study During a Pertussis Epidemic - Chen, Sainan; Wang, Yuqing; Li, Anrong; Jiang, Wujun; Xu, Qiuyan; Wu, Min; Chen, Zhengrong; Hao, Chuangli; Shao, Xunjun; Xu, Jun (Frontiers in Pediatrics, 2021)
Objective: In recent years, the incidence of Bordetella pertussis infection in infants and young children has been increasing. Multiple studies have suggested that B. pertussis may be the causative agent of bronchiolitis in infants and young children. However, the prevalence and clinic characteristic of B. pertussis in bronchiolitis is controversial. This prospective descriptive study evaluated the prevalence and clinical manifestations of infants and young children hospitalized for bronchiolitis with B. pertussis. Methods: Children hospitalized with bronchiolitis were eligible for a prospective study for 36 months from January 1, 2017, to December 31, 2019. Besides B. pertussis, 10 common respiratory viruses and Mycoplasma pneumoniae (MP) were confirmed by laboratory tests. Medical records of patients were reviewed for demographic, clinical characteristics, and laboratory examination. Results: A total of 1092 patients with bronchiolitis were admitted. B. pertussis was detected in 78/1092 (7.1%) patients. Of the 78 patients with B. pertussis bronchiolitis, co-infections occurred in 45 (57.7%) patients, most frequently with human rhinovirus (28/78, 35.9%), followed by MP (9/78, 11.4%) and human bocavirus (6/78, 7.7%). The peak incidence of B. pertussis infection was in May. A high leukocyte count could help distinguish B. pertussisassociated acute bronchiolitis from other acute bronchiolitis etiologies. After excluding co-infections, children with B. pertussisonly bronchiolitis exhibited a milder clinical presentation than those with RSV-only infection; also, children with MP-only and other pathogen infections revealed similar severity. The morbidity of B. pertussis was common (31/78, 39.7%) in infants with bronchiolitis under 3 months. Conclusion: In summary, B. pertussis is an important pathogen in children with bronchiolitis, and co-infection of B. pertussis with other viruses is common in bronchiolitis. B. pertussis should be considered when patients hospitalized with bronchiolitis present a longer course and have an elevated leukocyte count. Patients with B. pertussisassociated bronchiolitis present a milder clinical presentation.